HUbungan Hubungan Umur Dan Jenis Kelamin Terhadap Myofascial Trigger point Syndrome (MTPS) Pada Guru SMP Ar Rahman: Hubungan Umur Dan Jenis Kelamin Terhadap Myofascial Trigger point Syndrome (MTPS) Pada Guru SMP Ar Rahman - Ika Rahman Rahman (Miracle Journal, 2021)
A person's age and gender will be related to physical capacity to some extent. As a person ages, muscle strength, sensory and motor abilities will also decrease. Thus age will be related to the work of a person. In general, women only have physical strength 2/3 of the physical ability or muscle strength of men, but in certain cases women are more careful than men. To get high work power, it is necessary to try to divide the tasks between men and women according to their respective abilities, skill and limitations. MTPS complaints often occur in teacher workers related to age, resulting in complaints of muscle pain. This study aims to determine the relationship between Age and Gender with Myofascial Trigger Point Syndrome (MTPS) against teachers at Ar Rahman School Medan. This type of research uses an analytic design with a cross sectional design. The population and sample were 32 people. The results showed that there was a relationship between age (p value = <0.005) and there was no relationship between sex (p value = >0.05) with Myofascial Trigger Point Syndrome (MTPS). It is recommended for teachers to take advantage of the rest time to relax muscles in order to improve and improve physiological function.